Persepsi Pengunjung Terhadap Aktivitas UMKM Akhir Pekan Dalam Perspektif Kewilayahan di Padan Liu Burung Kabupaten Malinau - Mardiana Ulan Dari; Najma Nur Mawaddah; Mei Vita Romadon Ningrum; Aisyah Trees Sandy (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Micro, small, and medium enterprises (MSMEs) play an important role in supporting the local economy, especially in areas far from major urban centers. However, comprehensive studies linking visitors' perceptions of weekend MSME activities with regional perspectives are still limited. This study aims to analyze visitors' perceptions of MSME activities on weekends and the regional conditions of the Padan Liu Burung area, Malinau Regency, as a supporting space for these activities. Data were collected through questionnaires and semi-structured interviews with 42 respondents in January 2026, then analyzed using descriptive statistics on a 1–5 Likert scale and thematic analysis triangulated with survey findings. The results show that perceptions of MSME activities are in the high category (M = 4.149; SD = 0.512), especially in terms of liveliness and social interaction. Perceptions of regional conditions were also high (M = 3.868; SD = 0.583), but lower than the activity dimension, particularly in terms of cleanliness, supporting facilities, stall layout, and parking management. These findings indicate that the area has developed as a dynamic temporary public space but still faces challenges in spatial governance. Theoretically, this study proposes that the sustainability of temporary public spaces based on MSMEs requires a balance between experiential value and spatial governance, so that high social vitality needs to be balanced with adaptive infrastructure and spatial management capacity. These findings contribute to economic geography and regional planning studies in understanding the spatiotemporal dynamics of community-based local economic activities.